Anti-glioma Efficacy and Mechanism of Action of Tripolinolate A from Tripolium pannonicum - Chai, Weiyun; Chen, Lu; Lian, Xiao-Yuan; Zhang, Zhizhen (Planta Medica, 2018)
Tripolinolate A as a new bioactive phenolic ester was previously isolated from a halophyte of Tripolium pannonicum. However, the in vitro and in vivo anti-glioma effects and mechanism of tripolinolate A have not been investigated. This study has demonstrated that (1) tripolinolate A inhibited the proliferation of different glioma cells with IC50 values of 7.97 to 14.02 µM and had a significant inhibitory effect on the glioma growth in U87MG xenograft nude mice, (2) tripolinolate A induced apoptosis in glioma cells by downregulating the expressions of antiapoptotic proteins and arrested glioma cell cycle at the G2/M phase by reducing the expression levels of cell cycle regulators, and (3) tripolinolate A also remarkably reduced the expression levels of several glioma metabolic enzymes and transcription factors. All data together suggested that tripolinolate A had significant in vitro and in vivo anti-glioma effects and the regulation of multiple tumor-related regulators and transcription factors might be responsible for the activities of tripolinolate A against glioma.
Keywords: tripolinolate A; Tripolium pannonicum; Compositae; anti-glioma; apoptosis; cell cycle arrest; glioma metabolic enzymes